Novel Eco-Friendly Synthesis of Biosilver Nanoparticles as a Colorimetric Probe for Highly Selective Detection of Fe (III) Ions in Aqueous Solution - Nguyen Le Nhat Trang (Journal of Nanomaterials, 2021)
In this work, an eco-friendly approach for the synthesis of biogenic silver nanoparticles (bio-AgNPs) using botanical extracts in combination with an electrochemical process was carried out. We employed three types of plant extracts, including green tea leaf (GTE), grapefruit peel (GP), and mangosteen peel (MP) extracts to successfully synthesize the bio-AgNPs and optimized the experimental conditions aiming to get the highest synthetic yield. The formation of bio-AgNPs was monitored by UV-Vis spectroscopy via a surface plasmon resonance (SPR) band at about 420–430 nm. Transmission electron microscope (TEM) showed their spherical shape with the size range within 23–55 nm. While X-ray diffraction (XRD) analysis described in detail the crystalline structure of the bio-AgNPs with a face-centered cubic crystal lattice of metallic silver. The chemical bonding and elemental compositions of the bio-AgNPs were determined by Fourier Transform Infrared (FTIR) spectroscopy, in which organic compounds in the natural extracts not only acted as effective reductants but also capping agents for the fabricated bio-AgNPs. The prepared bio-AgNPs exhibited high stability and excellent dispersion for about four months. Based on the linear relationship between obtained SPR band intensity of bio-AgNP GTE in the presence of Fe (III) and concentration of Fe (III) ions, our bio-AgNP GTE can be used to develop a highly selective colorimetric sensor for the determination of Fe (III) ions within a linear range from 1 to 25 μM. According to that, the limit of detection (LOD) was recorded at approximately 0.532 μM, and the quantitative limit (LOQ) was calculated to be 1.77 μM. A detection mechanism was proposed through redox reactions between bio-AgNP GTE and Fe (III) ions. More interestingly, this method was successfully applied for the determination of Fe (III) ions in a lake water sample with percentage recovery of 107-150% and high reproducibility.